Non-destructive investigation of cellular level moisture distribution and morphological changes during drying of a plant-based food material. (May 2018) - Rahman, Mohammad M.; Joardder, Mohammad U.H.; Karim, Azharul
Abstract : This study investigates the complex microstructural changes and cell-level water transportation in plant-based food materials during drying, using X-ray micro-computed tomography (X-ray μCT). The investigations were performed on apple tissue to uncover the cellular level moisture distribution and the structural changes during convective drying at 50 °C, 60 °C, and 70 °C. Image analysis revealed that significant changes occurred in moisture content, and cell and pore size distribution with drying time and temperature. The moisture content determined using the X-ray μCT images was compared with that determined by the electronic moisture analyser (EMA) and good agreement was found. The results show a strong relationship between drying temperature, pore formation and deformation of the food material. At high drying temperature, the pore formation increased, which led to reduced shrinkage of the food material. The porosity of a sample of dried apple increased by 35% as drying temperature increased from 50 °C to 70 °C. However, a significant amount of cell rupture was observed during drying at the higher temperature. The cellular level moisture distribution profile confirmed that a traceable amount of water was still present in the centre cells of the tissue although the sample was deemed dried from the bulk moisture analysis. The findings of this study substantially enhance our understanding of instantaneous cellular level moisture distribution in a food sample over the time of drying. Highlights: Cellular level water distribution during drying of plant based food material. The cell rupture during drying was analysed. The intra and intercellular water distribution was explained. Non-destructive measurement of moisture content and porosity during drying. Significant changes in microstructure observed during drying at high temperature.